2013
DOI: 10.1128/genomea.00119-13
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Wohlfahrtiimonas chitiniclastica Strain SH04, Isolated from Chrysomya megacephala Collected from Pudong International Airport in China

Abstract: Wohlfahrtiimonas chitiniclastica bacilli that live in the larvae of a parasitic fly were recently isolated and are speculated to be the cause of fulminant sepsis. Here we report and analyze the complete genome sequence of Wohlfahrtiimonas chitiniclastica strain SH04. No complete genome sequence of a Wohlfahrtiimonas chitiniclastica isolate has been documented previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
(10 reference statements)
0
16
0
Order By: Relevance
“…[1]. Furthermore, another publication about the pathogen's occurrence in the insect species Hermetia illucens [3] and a report on a whole genome sequence of a W. chitiniclastica strain [11] appeared. To date, seven case reports and in total eight cases have been published on W. chitiniclastica infections in humans (case numbers: 1 [4], 2 [6], 3 [12], 4 [7], 5 [13], 6 [14], 7, 8 [15]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1]. Furthermore, another publication about the pathogen's occurrence in the insect species Hermetia illucens [3] and a report on a whole genome sequence of a W. chitiniclastica strain [11] appeared. To date, seven case reports and in total eight cases have been published on W. chitiniclastica infections in humans (case numbers: 1 [4], 2 [6], 3 [12], 4 [7], 5 [13], 6 [14], 7, 8 [15]).…”
Section: Resultsmentioning
confidence: 99%
“…The sequenced W. chitiniclastica strain SH04 has a genome size of 2·12 Mb, with an average G/C content of 43·48%. It contains 2006 open reading frames [11]. Further investigations revealed a high similarity to I. larvae , another bacterial species which is also commonly found in flies [1, 5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This bacterium has been isolated from larvae of the fly Wohlfahrtia magnifica, a serious parasite of livestock in eastern Europe, the Mediterranean, and Central Asia ( 3 ), but this fly is not usually seen in the United Kingdom. W. chitiniclastica has also been isolated in China from Chrysomya megacephala oriental latrine flies, a screwworm species common in tropical and subtropical regions that is a facultative cause of myiasis ( 4 , 5 ). A study from South Korea reported a new Wohlfahrtiimonas sp.…”
mentioning
confidence: 99%
“…To date, five Wohlfahrtiimonas species and no more than 20 W. chitiniclastica strains have been isolated in the world. Of these, only antibiotic sensitive strain SH04 has been sequenced completely in China ( 6 ).…”
Section: Genome Announcementmentioning
confidence: 99%